Comparing AI and Teacher Feedback: Student Insights on Creativity and Critical Thinking - Alfin Amaliah Zahroh; Mauly Halwat Hikmat; Agus Wijayanto (Dinasti International Journal of Education Management and Social Science, 2025)
This mixed-method study investigates students’ reflections on the strengths and limitations of feedback provided by ChatGPT compared to teacher feedback, particularly in relation to creativity, critical thinking, and content development in writing. The study was conducted in an English vocational school setting involving 40 students and 4 English teachers. Focus groups, in-depth interviews, and questionnaires were used to gather information in order to fully comprehend the opinions and experiences of the students. The analysis focused on how students evaluated the clarity, usefulness, and relevance of the feedback from both sources, as well as its impact on their ability to generate creative ideas, think critically, and improve the content of their writing. The findings suggest that teacher feedback remains essential for addressing students’ challenges in vocabulary, grammar, and idea expression by providing clarity, motivation, and personalized guidance. While ChatGPT contributes speed, accessibility, and consistency, it lacks the contextual depth and interpersonal dimension inherent in teacher feedback. Therefore, a hybrid feedback model that integrates human expertise with AI efficiency offers promising potential to optimize students’ writing development.